"Are you safe to talk?": perspectives of service providers on experiences of domestic violence during the COVID-19 pandemic - Leigh, Jenny K. (Journal of family violence, 2023)
This study aimed to better understand the factors driving reported trends in domestic violence during the COVID-19 pandemic, particularly the effect of the pandemic on survivors’ experiences of violence and ability to seek support. We conducted semi-structured qualitative interviews with 32 DV service providers operating in organizations across 24 U.S. cities. The majority of providers described a decrease in contact volume when shelter-in-place orders were first established, which they attributed to safety concerns, competing survival priorities, and miscommunication about what resources were available. For most organizations, this decrease was followed by an increase in contacts after the lifting of shelter-in-place orders, often surpassing typical contact counts from the pre-pandemic period. Providers identified survivors’ ability to return to some aspects of their pre-pandemic lives, increased stress levels, and increased lethality of cases as key factors driving this increase. In addition, providers described several unique challenges faced by DV survivors during the pandemic, such as the use of the virus as an additional tool for control by abusers and an exacerbated lack of social support. These findings provide insight into the lived experiences driving observed trends in DV rates during COVID-19. Understanding the impact of the pandemic on survivors can help to shape public health and policy interventions to better support this vulnerable population during future crises.